P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

Comparison of edoxaban and enoxaparin in a rat model of AlCl3-induced thrombosis of the superior sagittal sinus - M. Hachenberger; M. Yeniguen; L. Suenner; D. Hinchliffe; C. Mueller; A. Wietelmann; T. Gerriets; M. Tschernatsch; M. Juenemann; S. T. Gerner; T. R. Doeppner; H. B. Huttner; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Cerebral sinus venous thrombosis (CSVT) is an uncommon disease that is usually treated with anticoagulation (heparin, low-molecular heparin, or vitamin K-antagonists). We compared treatment with edoxaban, an oral factor Xa-antagonist, that has not been approved in patients with CSVT, with enoxaparin, a well-established therapy, in a rat model of CSVT. Fifty male Wistar rats were randomized into 5 groups (10 animals each) and subjected to aluminum chloride (AlCl3)-induced thrombosis of the superior sagittal sinus (SSS) or sham procedure. Animals with thrombosis of the SSS were treated with edoxaban, enoxaparin, or placebo. Diagnostic workup included neurological examination, MRI imaging, MR-flow measurements of the SSS, and immunohistochemical staining. Neurological examination revealed no differences between treatment groups. Seven days after initial thrombosis, flow in the SSS was lower in the active treatment group as compared to sham-operated animals ( p < 0.05). Flow in the SSS in the active treatment groups (edoxaban 1 h prior to thrombosis: 0.16 cm/s ± 0.06 cm/s; edoxaban 6 h after thrombosis: 0.13 cm/s ± 0.05 cm/s; enoxaparin: 0.13 cm/s ± 0.04 cm/s; placebo: 0.07 cm/s ± 0.02 cm/s) was higher as compared to placebo ( p < 0.05), but there were no differences between the active treatment groups ( p > 0.05). Immunohistochemical staining showed no differences in the actively treated animals. Edoxaban proved to be similar to enoxaparin in a model of experimental AlCl 3 -induced CSVT.

Role of obesity in a randomized placebo-controlled trial of difluoromethylornithine (DFMO) + sulindac for the prevention of sporadic colorectal adenomas - Jason A. Zell; Bruce S. Lin; Nikki Madson; Christine E. McLaren; Eugene W. Gerner; Frank L. Meyskens (Cancer Causes & Control, 2012)

Climate variability and campylobacter infection: an international study - R. Sari Kovats; Sally J. Edwards; Dominique Charron; John Cowden; Rennie M. D’Souza; Kristie L. Ebi; Charmaine Gauci; Peter Gerner-Smidt; Shakoor Hajat; Simon Hales; Gloria Hernández Pezzi; Bohumir Kriz; et al. (International Journal of Biometeorology, 2005)